First Optimization of Tomato Pomace in Diets for Tenebrio molitor (L.) (Coleoptera: Tenebrionidae) - Ferdinando Baldacchino; Anna Spagnoletta; Flutura Lamaj; Maria Luisa Vitale; Vincenzo Verrastro (Insects, 2023)
Tomato pomace (TP), an agricultural industrial waste product from the tomato processing industry, is valorized as a rearing substrate for Tenebrio molitor (L.). This study evaluated bran-based diets with increasing tomato pomace (0%, 27%, 41%, and 100%). Protein sources, such as brewer’s spent grain and yeast, were used in TP27 and TP41 diets to ensure equal protein contents to the control diet. Results showed no different for larval and pupal weights between diets; however, the time of development significantly increases in TP100 compared to all diets. The feed conversion rate progressively increases from 2.7 to 4.3, respectively, from the control to the TP100 diet. Conversely, lycopene and β-carotene increase in the larvae. The fatty acid composition improves by increasing polyunsaturated fatty acids (mainly α-linoleic acid). Although the best nutritional quality was obtained in T100, the TP41 is the optimal diet for balance between larval performance and qualitative improvement of larvae. Therefore, tomato pomace is suitable for the formulation of mealworm diets, even in high dosages, when supplemented with sustainable protein and carbohydrate sources.